(untitled) (Bangladesh Journal of Botany, 2019)
The work was carried out to compare the yield and quality of local Karacadag rice variety with the Osmancık-97 in conventional and organic agriculture conditions. In the organic agricultural conditions higher values were obtained compared to conventional conditions. Flowering took 82.6 days, 1000-kernel weight (31.38 g) and non-fractured rice yield were 61.75%. Local Karacadag rice variety under the organic conditions showed significantly higher values compared to Osmancık-97 breeding variety took 87.3 days for flowering, 128.2 days for ripening days. Plant height (84.1 cm), number of tillering in plants (2.82), number of bunches in the m2 (369.3), kernel number of bunch (56.5), bunch length (15.9 cm), biological yield (13440 kg/ha), yield for unit area (4681 kg/ha) and non-fractured rice yield (64.7%) were observed. While there was no difference between the two rice varieties with regards to the kernel weight of bunch. Local Karacadag variety proved its ability to adapt to the ecological conditions of the region. It is suggested that the cultivation of the Karacadag rice cultivar in organic agriculture conditions may be expanded in the region.